Museum Artifact Conservation Training for Social Science Educators and Students in Pontianak - Haris Firmansyah; Andang Firmansyah; Putri Tipa Anasi; Nur Meily Adlika; Yusawinur Barella; Venny Karolina; Aminuyati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The West Kalimantan Museum stores and exhibits a collection of items with historical, scientific, artistic, and cultural significance, primarily originating from West Kalimantan Province. It is crucial for social science educators and students in West Kalimantan to comprehend the significance of visiting the museum in person. This allows them to directly witness and study historical and cultural artifacts of West Kalimantan, thereby reinforcing the knowledge they acquire from books. Hence, social science education lecturers of Tanjungpura University organized a community service program known as "Pengabdian Kepada Masyarakat" (abbreviated as PKM) that invited both social science teachers and students of Pontianak to local museums for a visit. The objectives of this training encompassed two main goals. Firstly, it aimed to generate interest among teachers and students in discovering and familiarizing themselves with the museum. Secondly, it sought to enhance the knowledge of teachers and students regarding the conservation of the museum's collections. Following the training, the lecturers gathered feedback from participants via a Google form to assess their opinions regarding the museum collection and artifact preservation training. This data was then analyzed using a quantitative approach, and the results were presented using descriptive statistics. A total of 19 individuals responded to the survey, consisting of 7 teachers and 12 students. The results indicated that the participants had a positive response to the activity and expressed a request for similar programs to be conducted in the future.